Multiproduct Cost-Volume-Profit Model: A Resource Reallocation Approach for Decision Making. Issue 3 (1st September 2016) - Bergo, Gabriel Soares Zica; Lucas, Bruna Hoffmeister; Sobreiro, Vinicius Amorim; Nagano, Marcelo Seido
Abstract : This work addresses the problem of reallocating productive resources to maximize profit. Most contributions to the topic focus on developing or improving the Cost-Volume-Profit model to obtain solutions that provide an ideal mix of products before the data is given. In particular, some algorithms are available for the problem, such as the ones proposed by Kakumanu and Shao and Feng. However, these proposals do not consider the minimum number of units to be produced, and the reallocation of productive resources for each product is a problem found in these studies. Bearing this in mind, a new algorithm based on individual financial revenue is proposed. Computational results indicate that the proposed method can be utilized as a decision support system.